BIOFABRICATION OF SILVER NANOPARTICLES USING LEAVES OF GLORIOSA SUPERBA AND ITS ANTICANCER PROPERTIES - Bethu, Murali Satyanarayana; Rao J, Venkateswara (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: We aimed to synthesize the cost effective, one pot and an eco-friendly technique for the green synthesis of silver nanoparticles (AgNPs) using 1 mM of silver nitrate (AgNO3) solution through the aqueous leaf extracts of Gloriosa superba (GS) reducing and capping agent and its anticancer activity. Methods: Synthesis briefly 95 mL of 1 mM AgNO3 was taken into amber colored conical flask and added 5 mL of aqueous leaf extract of GS (pale brown) and incubated at room temperature in dark condition for about 24 hrs. Characterization of AgNPs derived from GS (GS-AgNPs) was performed with physiochemical techniques (ultraviolet, transmission electron microscope [TEM], X-ray diffraction [XRD], and thermal gravimetric analysis) and cytotoxicity by 3-(4,5-dimethylthiazo-2-yl)-2,5-diphenyltetrazolium bromide assay. Results: We synthesized cost effective, eco-friendly AgNPs were characterized by physiochemical techniques. The crystal nature of AgNP was studied by XRD. TEM studies reveal the morphology of GS-AgNPs, the size of the nanoparticle is 10-50 nm. The cytotoxicity of GS-AgNPs studied against the four human cancerous cell line DU145, SKOV3, PC3, and A549 but the GS-AgNPs are most sensitive toward the SKOV3 cell line. The minimum inhibitory concentration (IC) is 79.45±5.26, 61.80±4.27, 94.74±9.26, and 90.10±8.24 μg/mL, respectively. Morphological assessment of the SKOV3 cells was studied using AO/EB and Hoechst staining at IC50 concentration. Conclusion: The bio fabrication of the GS-AgNPs were simple, eco-friendly and one pot synthesis, it is used as an anticancer agent in future, pending further investigation.